An Empirical Study on Shareholders’ Awareness of Legal Rights and Protections Related to Dividends in India - Arangi, Venkataramana; Babu, N.Kishore (International Journal of Independent Research Studies, 2025)
This research paper explores how well Indian shareholders understand the legal rights and protections related to company dividend payments. Although dividend distribution is governed by well-established regulations—namely, the SEBI (Listing Obligations and Disclosure Requirements) Regulations and the Companies Act of 2013—many investors, especially individuals in the retail segment, remain unaware of these provisions. Despite the existence of strong legal safeguards, knowledge gaps still persist. To examine this issue, the study employed a structured questionnaire and surveyed 1,536 individual shareholders across different regions of India. The findings reveal that while most participants are familiar with the general idea of dividends, a substantial number are unclear about key aspects such as the timeline for payments, procedures for unclaimed dividends, and the role of the Investor Education and Protection Fund (IEPF). The data also indicates that awareness levels are influenced by several factors, including the shareholders’ level of education, prior investment experience, and exposure to financial literacy programs. These insights point to the need for better educational outreach and more transparent corporate communication to ensure shareholders are fully informed of their rights.